PERENCANAAN STOPWAY PADA UJUNG RUNWAY 01 DENGAN FLEXIBLE PAVEMENT DI BANDAR UDARA KALIMARAU BERAU - Habib Yogi Fauzi; Supriadi; Linda Winiasri (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Kalimarau Airport is a domestic airport that was founded in 1976 which is located in Berau Regency, East Borneo Province which has an important role in providing air transportation services. A stopway is a defined rectangular area on the ground at the end of the take-off path that is created as a suitable area where an aircraft can stop when it decides to cancel its take off. However, Kalimarau Airport doesn’t yet have a stopway at the end of the runway. The research began with collecting data such as air transport traffic data, data Aeronautical Information Publication at Kalimarau Airport in Berau. From those data, planning is carried put according to the method Federal Aviation Administration (FAA). And manual calculations using the FAARFIELD 1.41 application, the results obtained are the thickness of the flexible pavement structure in the area Stopway. Meanwhile, to calculate the value PCN using software COMFAA. This final project is designed how to plan pavement thickness using the FAA method. The planning of Flexible Pavement structure in the area of Stopway with the planned area is 2700 . For the results of the pavement structure using the FAARFIELD application, which is 32inch (81,12cm) with a PCN value of 57 F/C/X/T. based on the calculation of the RAB, the budget plan needed to carry out the Flexible Pavement structure work in the area of Stopway is Rp. 2.309.002.000,00.